Amsterdam koopt kunst : Gemeentelije Kunstaankopen 1988. (Amsterdam : Museum Fodor Amsterdam, 1989)
Andriesse, Jan ; Anema, Taco ; Bien, Waldo ; Blom, Ansuya ; Bollar, Gorki ; Boonstra, Marjoleine ; van den Broeck, Frank ; Van Den Broek, René ; Browne, Leslie ; Colton, Adam ; Commandeur, Jan ; Dam, Peter ; Domburg, Bart ; Fortuyn/O'Brien ; Frik, Helen ; Goedewaagen, Tobie ; Gunn, Reggy ; van Haaster, Bettie ; van Hanegem, Ab ; Heiden, Cécile Van Der ; Hijstek, Antoinette ; Homeijer, Kick ; Jolink, René ; Kaspers, Willem ; Kleerebezem, Jouke ; Kloosterboer, Klaas ; Lewkowicz, Stanislaw ; Mol, Pieter Laurens ; Noij, Toon ; Peeters, Jaqueline ; Pouls, Geer ; Robaard, Joke ; Schuil, Han ; Segers, Nicole ; Sierhuis, Jan ; Stansfield & Hooykaas ; Strang, Yvonne ; van Summeren, Ton ; Theuws, Roos ; van Tijn, Willeke ; Ulay ; Ventura, Julia ; Verhaar, Peter ; Versloot, Kees ; Vlugt, Harald ; Vroegindeweij, Leo ; Westra, Maria ; Wittering, Theo ; de Zeeuw, Mirjam ; Zijlmans, Sylvie
Amsterdam koopt kunst : Gemeentelije Kunstaankopen 1988, Museum Fodor, Amsterdam, 1989
Nederlands & Engels
boek